Comparison of Drug Availability in the Inner Ear After Oral, Transtympanic, and Combined Administration - Li, Yang; Kanzaki, Sho; Shibata, Shinsuke; Nakamura, Masaya; Ozaki, Masahiro; Okano, Hideyuki; Ogawa, Kaoru (Frontiers in Neurology, 2021)
Although combination of oral and transtympanic drug therapy (CT) has been proved more effective and safer for idiopathic sudden sensorineural hearing loss (ISSNHL) by some clinical trials, there are few laboratory researches on the pharmacokinetics in the inner ear following CT on account of structural limitations of the inner ear. The aim of the present study was to investigate the pharmacokinetic behaviors of CT in the inner ear of mice. Eighteen transgenic GFAP-Luc mice which express luciferase in cochlear spiral ganglion cells were divided into oral administration (OR) group, transtympanic injection route (TT) group and CT group, and luciferin was delivered into the inner ear of these mice through oral, transtympanic or combined routes, respectively. A new in vivo imaging system was used to observe luciferin/luciferase signals and the compare the pharmacokinetics of different administration routes in the inner ear of mice. Bioluminescence signals were observed in the inner ear 3.3 ± 2.6 min after CT, significantly earlier than that of OR group (15.8 ± 7.4 min). CT owned the longest reaching-peak time and largest area under the curve (AUC) among three groups. Compared to TT, CT had longer biological half-life and higher AUC value, but did not displayed stronger peak value. There were significant differences in the peak values between OR group and TT group and between OR group and CT group. This study suggests that the OR route is less effective than the TT or CT route, and combination of OR and TT can deliver more drugs into the inner ear and confer a longer therapeutic window, but cannot increase drug intensity.